Descriptions of two new endemic and cryptic species of Sitana Cuvier, 1829 from peninsular India - Deepak, V.; Khandekar, Akshay; Chaitanya, R.; Karanth, Praveen (Zootaxa, 2018)
Two new cryptic species of the agamid genus Sitana Cuvier, 1829 from Peninsular India are described herein. Sitana gokakensis sp. nov. from Gokak, Karnataka closely resembles Sitana thondalu sp. nov. from Nagarjuna Sagar, Andhra Pradesh. The two species can be distinguished based on their subtle morphological differences, genetic difference and geographic distribution. Sitana gokakensis sp. nov. have a relatively depressed head compared to Sitana thondalu sp. nov. Additionally, the vertebral scale counts differ in females of the two new species (Sitana gokakensis sp. nov. 45–47 vs Sitana thondalu sp. nov. 49–53). Genetic divergence between them is comparable to those between previously described Sitana species. Furthermore, the two new species are distributed ca. 500 km apart and are endemic to their respective landscapes that lie in similar latitudes of peninsular India. We urge the use of large sample size in new species descriptions especially those dealing with cryptic species like Sitana. The discovery of the two new cryptic species from these rocky terrains in peninsular India highlights need for more herpetological exploration in this region.